The Impact of Organizational Flexibility on Entrepreneurial Orientation Enhancement: A Field Study on Jordanian Information Technology Companies - Alkshali, Shaker; Badran, Arwa (Jordan Journal of Business Administration, 2020)
This study aimed to identify the impact of organizational flexibility on entrepreneurial orientation enhancement. It is a field study which has been applied on Jordanian information technology companies, where organizational flexibility represented the independent variable of the study. The study has adopted three dimensions to measure organizational flexibility, which are: structural flexibility, strategic flexibility, and operations flexibility. As for the dependent variable which is entrepreneurial orientation, it has been measured by three dimensions which are: risk taking, innovation and proactivity. The study was conducted on a sample of (141) workers from the investigated companies. For the sake of achieving this study’s objectives, the researchers have developed a questionnaire to collect data from the workers based on several previous studies, where the questionnaire forms were distributed among the individuals randomly. The results of the study indicated that applying the organizational flexibility dimensions in these companies was at high levels, where operations flexibility dimension came in advance of the others. With regards to the level of applying entrepreneurial orientation dimensions, it was also high, where the dimension of innovation was the highest. Also, the results showed a significant effect of organizational flexibility on entrepreneurial orientation in the investigated companies. In light of the study’s findings, some recommendations were submitted, such as: necessity of Jordanian information technology companies to review their operations, systems and relevant work procedures, with the emphasis to take into consideration applying this review collectively by creating special teams and providing freedom for these groups, in addition to the necessity of developing a system to collect, classify and analyze data and information whether related to operations or beneficiaries.